The hippocampus under influence: structural effects of synthetic and natural psychotropic medications - Melissa Santaya; Halford Warlick; Causicaa Chandramohan; Prathmica Chandramohan; Armena Jafarmadar; Ernesto Joubran; Marianne Koleng; Christina Regine Owens-Charles; Jorge Rubinos Rodriguez; Madeline Sardinas; Leah Simon; Stephanie Singer; et al. (Molecular Biology Reports, 2026)

Worldwide Soundscapes: A Synthesis of Passive Acoustic Monitoring Across Realms - Kevin F. A. Darras; Rodney A. Rountree; Steven L. Van Wilgenburg; Anna F. Cord; Frederik Pitz; Youfang Chen; Lijun Dong; Agnès Rocquencourt; Camille Desjonquères; Patrick Mauritz Diaz; Tzu‐Hao Lin; Théophile Turco; et al. (Global Ecology and Biogeography, 2025)
Aim The urgency for remote, reliable and scalable biodiversity monitoring amidst mounting human pressures on ecosystems has sparked worldwide interest in Passive Acoustic Monitoring (PAM), which can track life underwater and on land. However, we lack a unified methodology to report this sampling effort and a comprehensive overview of PAM coverage to gauge its potential as a global research and monitoring tool. To address this gap, we created the Worldwide Soundscapes project, a collaborative network and growing database comprising metadata from 416 datasets across all realms (terrestrial, marine, freshwater and subterranean). Location Worldwide, 12,343 sites, all ecosystem types. Time Period 1991 to present. Major Taxa Studied All soniferous taxa. Methods We synthesise sampling coverage across spatial, temporal and ecological scales using metadata describing sampling locations, deployment schedules, focal taxa and audio recording parameters. We explore global trends in biological, anthropogenic and geophysical sounds based on 168 selected recordings from 12 ecosystems across all realms. Results Terrestrial sampling is spatially denser (46 sites per million square kilometre—Mkm 2 ) than aquatic sampling (0.3 and 1.8 sites/Mkm 2 in oceans and fresh water) with only two subterranean datasets. Although diel and lunar cycles are well sampled across realms, only marine datasets (55%) comprehensively sample all seasons. Across the 12 ecosystems selected for exploring global acoustic trends, biological sounds showed contrasting diel patterns across ecosystems, declined with distance from the Equator, and were negatively correlated with anthropogenic sounds. Main Conclusions PAM can inform macroecological studies as well as global conservation and phenology syntheses, but representation can be improved by expanding terrestrial taxonomic scope, sampling coverage in the high seas and subterranean ecosystems, and spatio‐temporal replication in freshwater habitats. Overall, this worldwide PAM network holds promise to support cross‐realm biodiversity research and monitoring efforts.

Urinary metabolite concentrations of phthalate and plasticizers in infancy and childhood in the UNC baby connectome project - Jake E. Thistle; Chih-Wei Liu; Julia E. Rager; Alison B. Singer; Dazhe Chen; Cherrel K. Manley; Joseph Piven; John H. Gilmore; Alexander P. Keil; Anne P. Starling; Hongtu Zhu; Weili Lin; et al. (Environmental Research, 2024)

Genomic Analysis of Xylose Metabolism in Members of the Deinoccocus-Thermus Phylum from Thermophilic Biomass-Deconstructing Bacterial Consortia - Yu-Wei Wu; Chijioke Joshua; Stephanie A. Eichorst; John M. Gladden; Blake A. Simmons; Steven W. Singer (BioEnergy Research, 2015)

Community dynamics of cellulose‐adapted thermophilic bacterial consortia - Stephanie A. Eichorst; Patanjali Varanasi; Vatalie Stavila; Marcin Zemla; Manfred Auer; Seema Singh; Blake A. Simmons; Steven W. Singer (Environmental Microbiology, 2013)
Summary Enzymatic hydrolysis of cellulose is a key process in the global carbon cycle and the industrial conversion of biomass to biofuels. In natural environments, cellulose hydrolysis is predominately performed by microbial communities. However, detailed understanding of bacterial cellulose hydrolysis is primarily confined to a few model isolates. Developing models for cellulose hydrolysis by mixed microbial consortia will complement these isolate studies and may reveal new mechanisms for cellulose deconstruction. Microbial communities were adapted to microcrystalline cellulose under aerobic, thermophilic conditions using green waste compost as the inoculum to study cellulose hydrolysis in a microbial consortium. This adaptation selected for three dominant taxa – the F irmicutes, B acteroidetes and T hermus . A high‐resolution profile of community development during the enrichment demonstrated a community transition from F irmicutes to a novel B acteroidetes population that clusters in the C hitinophagaceae family. A representative strain of this population, strain NYFB , was successfully isolated, and sequencing of a nearly full‐length 16S rRNA gene demonstrated that it was only 86% identical compared with other validated strains in the phylum B acteroidetes . Strain NYFB grew well on soluble polysaccharide substrates, but grew poorly on insoluble polysaccharide substrates. Similar communities were observed in companion thermophilic enrichments on insoluble wheat arabinoxylan, a hemicellulosic substrate, suggesting a common model for deconstruction of plant polysaccharides. Combining observations of community dynamics and the physiology of strain NYFB , a cooperative successional model for polysaccharide hydrolysis by the F irmicutes and B acteroidetes in the thermophilic cellulolytic consortia is proposed.